(untitled) (Research, Society and Development, 2023)
The urgency of innovation in the energy field, combined with environmental concerns and the high generation of waste on the world stage, increasingly encourages the use of anaerobic digestion techniques as a thriving technology for the treatment of such environmental liabilities and the production of biogas. Thus, the use of a biodigester for biogas production is one of the possible ways to take advantage of the renewable energy potential available in the environment. Thus, this research aims to evaluate the potential of biogas production in the operation of a batch bench biodigester, from waste produced in a popular restaurant located in the neighborhood of Rosa Elze, in the city of São Cristóvão, using it as an inoculum goat manure, in adverse concentration (0, 1, 2 and 3%). The biodigesters used in the study were developed from the reuse of polyethylene terephthalate (PET) bottles and operated for 21 days at a temperature of 25 °C. With this, it was possible to verify the evolution of the daily generation of biogas through the anaerobic decomposition of organic matter and also to monitor the temperature and pH of the samples. According to the results found in this research, the best condition for the production of biogas was with a concentration of 3% of inoculum, with a pH of 7.12, that is, with pH adjustment, obtaining a production of 18 mL of biogas. In the energy generation potential, the present work obtained a generation of 321 kWh/month, indicating a gain of R157.97/month with the biogas produced by the food residues of the popular restaurant. They indicate anaerobic digestion as a sustainable process, being efficient and with low cost.